New and little known earthworm species from Greece (Oligochaeta: Lumbricidae, Acanthodrilidae) - Szederjesi, Tímea; Csuzdi, Csaba (Zootaxa, 2012)
The results of the soil zoology collecting trips to Greece carried out by the members of the Hungarian Natural HistoryMuseum between the years 2006 and 2011 are summarized. Altogether 31 earthworm species were collected includingtwo species new to science; Eisenia oreophila and Dendrobaena retrosella spp. nov. Further six species proved to be newfor the fauna of Greece: Dendrobaena balcanica (Černosvitov, 1937), D. hrabei (Černosvitov, 1934), D. octaedra (Savi-gny, 1826), Eiseniella neapolitana (Örley, 1885), Fitzingeria loebli Zicsi, 1985 and Helodrilus vagneri Mršić, 1991. Fur-thermore, Octodrilus peleensis Michalis, 1995 is proposed to be a synonym of Oc. complanatus. The resulting list of earthworms recorded for the fauna of Greece contains 54 lumbricid species.